Sobre el impacto de la infraestructura pública en el producto y el crecimiento económico: Colombia 1950-2000 - Tenorio, Jorge Andrés (Sociedad y Economía, 2007)
Bearing in mind the structural change from 1980, the scale effects of education on humancapital, and the stock of physical capital, this paper estimates the impact of public infrastmctureon GDP and economic growth of Colombia. The analysis yields significant evidence oftechnological complementarities between prívate and public factors. The diminishing trend oftotal factor productivity (TFP) since the 70's, is the main cause of the diminishing trend ofeconomic growth in the long run, which begins in the 70 's and is deepened in the 90 's.